ANALISIS PERKEMBANGAN PERKEBUNAN KELAPA SAWIT DI KABUPATEN TANAH BUMBU - NI KETUT SUDIANTI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research was conducted to know the productivity of oil palm plantation in Tanah Bumbu Regency and how the contribution of oil palm development to the regional income in Tanah Bumbu Regency. Data analysis techniques in this study using quantitative descriptive analysis techniques. Given the peroduktivitas of oil palm plantations in Tanah Bumbu regency from the last five years experienced a good development is evident from the results of oil palm plantation productivity in 2016 reached 19,000 (Ton / Ha). The contribution of the palm oil sector in 2016 to Rp 34.818.670.368 means that the commodity of palm oil can boost economic growth and increase capital in Tanah Bumbu Regency. Keywords : Productivity of Oil Palm Plantation, Contribution to Local Income.